Kebebasan Beragama di Universitas Negeri Jakarta : Hak dan Batasan Mahasiswa dalam Menjalankan Keyakinan - Adisti Indah Pramesti; Gita Lia Febrianti; Mikel Adi Leonsai; Abdul Fadhil (Pusat Riset dan Inovasi Nasional, 2025)
Freedom of religion is one of the human rights recognized internationally and protected by the Indonesian Constitution. In the case of Jakarta State University (UNJ), this freedom supports the development of students' identities and personalities as diverse individuals. As a higher education institution, UNJ has the responsibility to guarantee this freedom by providing worship services, space for freedom of expression, and support for religious activities. However, this freedom is also subject to certain restrictions in order to maintain harmony between religious communities on campus. The purpose of this article is to analyze the importance of religious freedom at UNJ, its practical challenges, and the institution's efforts to create a tolerant and inclusive environment.